Memahami perilaku konsumen dalam pengambilan keputusan di era digital - Efendi, Muhammad Alief Rafa (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has changed the way consumers make purchasing decisions. Increasingly easy access to information through the internet and social media has made consumers more active in searching, comparing, and evaluating products before purchasing. This study aims to understand how consumer behavior is formed and changed in the digital era. The method used is a literature study by reviewing various sources related to consumer behavior and technological developments. The results of the discussion indicate that factors such as ease of information access, user reviews, trends on social media, and psychological factors such as motivation and lifestyle significantly influence consumer decisions. Furthermore, the decision-making process has become faster and more dynamic than before. However, this condition also poses risks such as consumptive behavior and dependence on public opinion. Therefore, consumers are required to be wiser and more critical in making decisions. This research is expected to provide a more relevant understanding of consumer behavior in the digital era, both for academics and business practitioners.